Ekosemen Sebagai Media Perekat Pengganti Semen Untuk Beton - Sastra, Marhadi; Pribadi R, Juli Ardita (P3M Politeknik Negeri Banjarmasin, 2018)
Waste is a serious problem faced at this time. A lot of pollution and diseases caused by waste, therefore many efforts are made so that waste can be utilized even contain economic value. One of the utilization of waste is as an eco-cement used as a substitute for cement. This study used the concrete quality of the plan fc '= 10 MPa and fc' = 20 MPa, the making of concrete utilized waste ash in lieu of cement in predetermined quantities, waste ash obtained from organic waste and inorganic waste that was burned to ash and then filtered using 100 and 200 sieves. Variations of ash addition of 0%, 10%, 20%, 30%, 40% and 50% of the volume ratio. Age of concrete testing was 7, 14 and 28 days. The results obtained from the test indicate that the material used met a predetermined standard, with the variation of the concrete weight mixture of concrete unchanged. From the concrete strength test result for fc '= 10 MPa, the best concrete mixed variation is 20% with compressive strength equal to 12,76 MPa at 28 day age, fc = 20 MPa concrete quality with best mix variation 20% has compressive strength of 17.29 MPa, the largest compressive strength value compared with the compressive strength of concrete containing ash, the compressive strength difference of 13.8% lower than the normal compressive strength of the concrete, while the effect of each mixture variation on the age of concrete is linear; with the increase of the age, the compressive strength tends to increase.